Pengembangan Arena Bermain dan Kreatifitas Anak Tradisional Kalurahan Giriasih Sebagai Daya Tarik Wisata Pedesaan - Agus Taufiq Taufiq; Pratikno Hidayat (Jurnal Abdimas Madani dan Lestari (JAMALI), 2023)
The tourism industry is growing and developing rapidly in Gunungkidul, one of the Giriasih Village Government's efforts to develop tourism is by successfully lifting the Pego Cave water source for the community's water needs, then turning the Bembem Embung which was originally used as a place for the community to meet water needs into a Tourism Object. Embung Bembem Tourism Park is the main tourist destination in the Giriasih Village which is equipped with parking facilities, gazebos, bathrooms and a joglo. In addition, there are also kayak and duck boat facilities. as well as food and drink stalls. In order to attract more tourists, it is necessary to add supporting facilities so that the Embung Bembem Tourism Park is more attractive to visit, this is the background for this service to be carried out. Assistance to POKDARWIS Tirta Lestari to be able to develop the potential that exists in the Embung Bembem Tourism Park and other potentials in the Giriasih Village has the aim of overcoming problems: 1) Lack of tourism management capability; 2) Limited knowledge of human resources in developing tour packages. Methods used by Servants 1) Developing children's play areas, 2) Making Selfie Areas and 3) Making educational tour packages. The outputs achieved are in the form of: 1) Children's play area; 2) Selfie area and 3) Educational tour packages.